Evaluation of an intraoral mouthguard as used by a patient with epilepsy – case report - Gawlak, Dominika; Świderska, Magdalena; Skalska, Karolina; Łojszczyk, Robert; Mańka-Malara, Katarzyna (Journal of Stomatology, 2017)
Introduction. Epilepsy is one of neurological chronic diseases characterized by sudden changes in behaviour, loss of consciousness, seizures or tonic skeletal muscles tone of varying intensity, which may be caused by uncontrollable discharges of grey matter cells, which furthermore results in temporary brain dysfunction. It may be idiopathic or due to stress, temperature, sleep deprivation and alcohol consumption. Patients with such a disease often sustain injuries in the stomatognathic area. However, no standard proceedings regarding protection of its structures during seizures have been established. Aim of the study. To assess intraoral mouthguards as worn by a patient with epilepsy who is often subject to injuries in the oral cavity area during seizures. Material and methods. Three intraoral mouthguards made of various polymeric materials identical to those worn by sportsmen doing sports with a traumatic potential were assessed in a questionnaire. On its basis, the use of the ethyl polymetacrylan mouthguard during epileptic seizures and its impact on injuries in the oral cavity area was reviewed and assessed. Results. A mouthguard of Impak material made at a split ratio of powder to liquid of 1.25:1 and